2016
DOI: 10.1051/0004-6361/201629194
|View full text |Cite
|
Sign up to set email alerts
|

A new sample of X-ray selected narrow emission-line galaxies

Abstract: A sample of X-ray and optically selected narrow emission-line galaxies (769 sources) from the 3XMM catalogue cross-correlated with SDSS (DR9) catalogue has been studied. Narrow-emission line active galactic nuclei (AGN; type-2) have been selected on the basis of their emission line ratios and/or X-ray luminosity. We have looked for X-ray unobscured type-2 AGN. As X-ray spectra were not available for our whole sample, we have checked the reliability of using the X-ray hardness ratio (HR) as a probe of the level… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 106 publications
1
5
0
Order By: Relevance
“…Under the current framework of the preferred (though still being improved) unified model (Antonucci 1993;Netzer 2015), type-1 AGN and type-2 AGN have exactly the same central structures of narrow emission line regions (NLRs) and broad emission line regions (BLRs; that is, the two essential structures of AGN), although the BLRs are seriously obscured by their central dust torus, leading to no apparent broad optical emission lines being detected in type-2 AGN. The well-detected polarized broad emission lines in type-2 AGN, such as in the well-discussed results in Antonucci & Miller (1985), Tran (2001Tran ( , 2003, Nagao et al (2004), Cardamone et al (2007), Shi et al (2010), Barth et al (2014), Pons & Watson (2016), and Savic et al (2018), provide robust evidence to strongly support the hypothesis of hidden BLRs in type-2 AGN. Certainly, there is one precious subclass of true type-2 AGN: a type-2 AGN without a hidden BLR.…”
Section: Introductionsupporting
confidence: 57%
“…Under the current framework of the preferred (though still being improved) unified model (Antonucci 1993;Netzer 2015), type-1 AGN and type-2 AGN have exactly the same central structures of narrow emission line regions (NLRs) and broad emission line regions (BLRs; that is, the two essential structures of AGN), although the BLRs are seriously obscured by their central dust torus, leading to no apparent broad optical emission lines being detected in type-2 AGN. The well-detected polarized broad emission lines in type-2 AGN, such as in the well-discussed results in Antonucci & Miller (1985), Tran (2001Tran ( , 2003, Nagao et al (2004), Cardamone et al (2007), Shi et al (2010), Barth et al (2014), Pons & Watson (2016), and Savic et al (2018), provide robust evidence to strongly support the hypothesis of hidden BLRs in type-2 AGN. Certainly, there is one precious subclass of true type-2 AGN: a type-2 AGN without a hidden BLR.…”
Section: Introductionsupporting
confidence: 57%
“…Interestingly, based on the pioneering work on the study of polarized broad emission lines in type 2 AGN by Antonucci & Miller (1985), Tran (2001), Tran (2003), Nagao et al (2004), Cardamone et al (2007), and followed by Shi et al (2010), Barth et al (2014), Zhang (2014), Li et al (2015), Pons & Watson (2016), and Zhang et al (2021c), there is one special kind of AGN: true type 2 AGN (or AGN with no hidden BLRs, or BLR-less AGN or unobscured type 2 AGN in the literature) that have no expected hidden central BLRs. There are about 30 Seyfert 2 galaxies with no hidden BLRs reported in Tran (2001), andTran (2003), due to the lack of polarized broad emission lines.…”
Section: Introductionmentioning
confidence: 99%
“…A true type 2 AGN candidate, SDSS J0120, is reported by Li et al (2015), through its longterm variability properties but with no-detected broad emission lines. A small sample of true type 2 AGN candidates is reported in Pons & Watson (2016) based on their properties of unobscured X-ray emission. More recently, Zhang et al (2021c) reported the composite galaxy SDSS J1039 as a true type 2 AGN candidate based on its long-term variabilities and its apparent loss of broad optical Balmer emission lines.…”
Section: Introductionmentioning
confidence: 99%
“…2018to Aug. 2021, well applied to re-confirm that the SDSS J0838 is a Type-2 AGN, not a true Type-2 AGN without hidden central broad emission line regions. More discussions on properties of true type-2 AGN with apparent variabilities can be found in Barth et al (2014); Li et al (2015); Pons & Watson (2016); Zhang et al (2021c).…”
Section: Photometric Variabilitiesmentioning
confidence: 99%